Modified algorithm for image watermarking using 2D-DCT and elgamal cryptosystem / Nur Azien Yazid, Kamilah Abdullah and Suhaila Abd Halim - Yazid, Nur Azien; Abdullah, Kamilah; Abd Halim, Suhaila (Universiti Teknologi MARA Cawangan Pulau Pinang, 2019)
Image watermarking embeds identifying information in an image in such a manner that it cannot easily be removed. For the past several years, image digital watermarking has become a necessary element used for hid ing secret image and enabling secured communication such as privacy, confidentiality, authentication and data integrity. Although numerous watermarking schemes are present in grayscale images, the present work focuses on the RGB color image. This study proposed a new hybrid method that would satisfy the essential needs of modern image watermarking. The color image watermarking is based on the 2D Discrete Cosine Transform and Egamal cryptosystem.The 2D Discrete Cosine Transform depends on the matrix products, while the ElGamal cryptosystem depends on the discrete logarithm problem. The cryptosystem is combined with existing Arnold transform in watermarking algorithm to enhance the security of secret image. Value of Peak Signal to Noise Ratio was taken as performance evaluation parameters. On the whole, the performance evaluation shows that combining the two algorithms improved the performance of image watermarking.